Kerangka Kerja Integrasi Kecerdasan Buatan (AI) untuk Formulasi Strategi Bisnis Digital Berbasis Data - Sari, Muh Masri (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The rapid development of digital technology has encouraged organizations to adopt a data-driven decision-making (DDDM) approach as a primary strategy for maintaining competitiveness amidst a complex and dynamic business landscape. This approach enables more accurate, faster, and fact-based decision-making, thereby enhancing the effectiveness of business strategies. This article aims to formulate a conceptual framework that facilitates the integration of Artificial Intelligence (AI) into the digital business strategy formulation process. This research uses a qualitative approach through a thematic content analysis of reputable scientific literature published between 2019 and 2024. The results of the study indicate that AI plays a strategic role in improving operational efficiency, driving innovation, and strengthening organizational responsiveness to rapid changes in the external environment. AI functions not only as a data analysis tool but also as a driver of business model transformation through predictive capabilities, process automation, and service personalization. However, the successful integration of AI into DDDM is inseparable from several important prerequisites. Key determining factors include adequate digital infrastructure readiness, visionary leadership capable of guiding strategic change, and competent human resources who understand both the technical aspects and strategic implications of AI. On the other hand, challenges faced include organizational cultural resistance to the adoption of new technologies, low data quality and completeness, and a digital skills gap among employees. The conceptual framework proposed in this article maps the linkages between organizational capabilities, AI-enhanced DDDM mechanisms, and the achievement of strategic objectives. This framework is designed to assist organizations in systematically planning, implementing, and evaluating AI integration initiatives. Furthermore, this article provides practical recommendations for business stakeholders in Indonesia, including the importance of investing in digital infrastructure, developing human resource competencies, and establishing an organizational culture that is adaptive to technological innovation.